TALABA-JASLARDÍ GLOBALLASÍW PROCESINDE MÁNÁWIY TARBIYALAWDÍŃ INNOVACIYALÍQ MEXANIZMLERI - Primbetov, K.T. (SCIENCE and SOCIETY, 2026)
In identifying the global problems of humanity, the real processes and forms of globalization, the youth parameter stands first. It is young people who suffer economically and socially and may end up in the center of events. First of all, young people must master the renewing secular ethics and learn to live on its basis.